Socio-economic development of the regions at the beginning of the 2020s - Korenik, Stanisław (Rozwój społeczno-gospodarczy regionów na początku trzeciej dekady XXI wieku, 2021)
The modern economy is characterized by rapid, multidirectional, even turbulent transformations, where the COVID-19 pandemic has come to the fore, beyond the current causes (shaping the new economy, globalization, financialization, etc.). As part of these changes, the situation of individual regions has begun to change. Regions characterized by an economy with multifunctional modern structures adapt better to the transformations that have occurred and the so-called new normality.
Biblioteka Regionalisty, 2021, Nr 21, s. 41-51
Keywords: COVID-19; pandemic; socio-economic region; new economy; globalization; regional development; innovation; pandemia; region społeczno-ekonomiczny; nowa gospodarka; globalizacja; rozwój regionu; innowacje